Dietary supplementation with 15% tomato pomace (Solanum lycopersicum L.) improves sperm production and antioxidant status in aged male broiler breeders - Amir Mosayyeb Zadeh; Seyyed Ali Mirghelenj; Mohsen Daneshyar; Mohsen Eslami; Mohammad Amir Karimi Torshizi; Mahdi Zhandi; Touba Nadri; John Patrick Kastelic; Peyman Hasanloo; Mehdi Nabiloo (Poultry Science)
The objective was to investigate effects of dietary tomato pomace (TP) and L-Arginine (L-Arg; 10% above nutritional recommendation) in aged male broiler breeders. Thirty male broiler breeders (Ross 308), 58 wk old, were randomly and equally allocated into five experimental groups: basal diet (C); 5% TP-supplemented (T-5); 10% TP-supplemented (T-10); 15% TP-supplemented (T-15); and L-Arg supplemented (L-10) groups. In contrast to the Control and TP-supplemented groups, sperm of L-10 roosters had higher C14:1, C16:0 and C18:1 n-9c proportions, total saturated fatty acid (FA) contents, and n-6:n-3 ratios, but a lower C22:4 n-6 content (P<0.05). However, sperm of T-15 roosters had increased C18:2 n-6, C22:6 n-3 and total unsaturated FA contents but reduced n-6:n-3 ratios compared to Control birds (P<0.05). Additionally, serum of T-15 roosters had lower cholesterol and triglyceride (TG) concentrations, along with decreased aspartate aminotransferase (AST) activity (P<0.05). In serum of T-15 and L-10 roosters, there were increases (P<0.05) in total antioxidant capacity (TAC) and uric acid (UA) and a reduction (P<0.05) in malondialdehyde (MDA) concentration. The T-15 roosters had higher (P<0.05) serum testosterone concentration and testes glutathione peroxidase (GPx) activity. Superoxide dismutase (SOD) content was reduced (P<0.05) in L-10 roosters. Seminiferous tubule diameter (STD) and seminiferous epithelium thickness (SET) were increased in all groups fed TP (P<0.05) and T-10 and T-15 roosters had increases (P<0.05) in tubular differentiation indices (TDI). The T-15 and L-10 groups had higher mRNA expressions of AKT1 and Nrf2 (P<0.05). In conclusion, in aged male broiler breeders, up to 15% TP supplementation is recommended to improve reproductive performance by enhancing testes histology and antioxidant status.